THE FORMATION OF INFORMATICS COMPETENCY FOR FUTURE COMPUTER SCIENCE TEACHERS IN THE PROCESS OF STUDYING COMPUTER MATHEMATICS - Chernenko, Varvara (Fizyko-matematychna osvita, 2021)
Relevance and expediency of introduction of a training course of computer mathematics for students of “Secondary Education (Computer Science)” is caused by necessity of use of computer equipment with the corresponding software almost in all areas of human activity; the fact that computer mathematics is one of priority directions of research work both in the field of mathematical sciences, and in the field of computer science. Computer mathematics is a field of applied computer science in which problems of development, implementation and use of information technologies for solving mathematical problems are studied. The purpose of teaching computer mathematics is to study and use computer mathematics systems by students to solve applied problems; to master the conceptual and terminological base of modern computer science as a fundamental science; to master theoretical fundamentals of computer science related to formal systems, knowledge bases and models of their representation, models and algorithms of decision making. Formulation of the problem. The study of computer mathematics by future computer science teachers and the use of modern systems of computer mathematics to solve applied problems, creates their system of professional competencies, in particular, informatics competencies in computer mathematics, informatics and mathematical competencies and skills to use modern information technology to analyze mathematical models of processes and phenomena from a variety of fields of knowledge and human activities. Materials and methods. To achieve this goal, the following research methods were used: analysis of scientific and pedagogical literature on the research topic; analysis of curricula, work programs and manuals on the subject "Computer Mathematics"; empirical methods (questionnaire, conversation, pedagogical observation, modeling). Results. This paper has built the model of building informatics competence within the professional competence of the future computer science teacher at the expense of integration of mathematical and information knowledge on the basis of mathematical modeling in environments of systems of computer mathematics, as these systems are an effective means of realization of inter-subject connections of computer science with other subjects of a natural-mathematical cycle. Conclusions. The study of "Computer Mathematics" courses by future computer science teachers, using computer mathematics systems, contributes to the formation of components of the information competence system in the field of information, mathematical and computer modeling.